2005
DOI: 10.3200/gntp.166.1.117-129
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stating Problems in Bilingual Students' First and Second Languages on Solving Mathematical Word Problems

Abstract: Researchers have suggested that among bilinguals, solving word problems in mathematics is influenced by linguistic factors (K. Durkin & B. Shire, 1991; L. Verschaffel, B. Greer, & E. De Corte, 2000). Others have suggested that students exhibit a strong tendency to exclude real-world constraints in solving mathematics word problems (L. Verschaffel, E. De Corte, & S. Lasure, 1994). In the present study, the authors explored the effects of stating word problems in either Filipino or English on how Filipino-Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 11 publications
3
25
1
2
Order By: Relevance
“…It has been found that bilingual students with high level proficiency in both their languages outperform their peers in mathematics for whom one language was dominant, or who had low competency in both their languages. This language impact is evident even after potential influencing variables are accounted for (Bernardo, 1999(Bernardo, , 2002Bernardo & Calleja, 2005;Clarkson, 1991a;Clarkson & Dawe, 1994Clarkson & Galbraith, 1992;Dawe, 1983;Erktin & Akyel, 2005;Latu, 2005). Clarkson and Dawe (1994) suggested a need to explore how bilingual students used their languages when doing mathematics, since it was likely that it was in these processes that the cognitive benefit accrued.…”
Section: Mathematical Learning and Bilingualismmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that bilingual students with high level proficiency in both their languages outperform their peers in mathematics for whom one language was dominant, or who had low competency in both their languages. This language impact is evident even after potential influencing variables are accounted for (Bernardo, 1999(Bernardo, , 2002Bernardo & Calleja, 2005;Clarkson, 1991a;Clarkson & Dawe, 1994Clarkson & Galbraith, 1992;Dawe, 1983;Erktin & Akyel, 2005;Latu, 2005). Clarkson and Dawe (1994) suggested a need to explore how bilingual students used their languages when doing mathematics, since it was likely that it was in these processes that the cognitive benefit accrued.…”
Section: Mathematical Learning and Bilingualismmentioning
confidence: 99%
“…Again difficulties with this aspect of the solution strategy prompt bilingual students to switch languages (Bernardo, 1999;Bernardo & Calleja, 2005;Linthorne & Doolan, 2003;O'Connell, 2000). Hence, when asked to solve what for them is a difficult mathematical problem, bilingual students may at any stage in the solving process try and use their L1 as part of their solution strategy.…”
Section: Mathematical Learning and Bilingualismmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu farklılığın nedeni eğitim fakültesindeki öğretim elemanlarının öğretme şekilleri olabilir. Bu bulgu Bernardo ve Calleja (2005)'nın bulgusu ile örtüşmektedir. Bernardo ve Calleja (2005) yaptıkları çalışmada öğretmenlerin bir konuyu öğretme şekli neticesinde öğrenme üzerine epistemolojik inançların yön bulduğunu bulmuşlardır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Bu bulgu Bernardo ve Calleja (2005)'nın bulgusu ile örtüşmektedir. Bernardo ve Calleja (2005) yaptıkları çalışmada öğretmenlerin bir konuyu öğretme şekli neticesinde öğrenme üzerine epistemolojik inançların yön bulduğunu bulmuşlardır. Yine, Gupta ve Elby (2011) ve Muis ve Gierus (2014 öğrencilerin işlemsel ve kavramsal bilgiyi birbirinden tamamen ayırdıklarını ve bu durumun öğrencilerin epistemolojik inançlarını etkilediğini belirtmektedirler.…”
Section: Tartışma Sonuç Ve öNerilerunclassified